Retour de l’absent - Claire Demesmay; Sabine Russ-Sattar; Katrin Sold (Revue des Mondes Musulmans et de la Méditerranée, 2018)
In the following article we explore the impact of the events of 2011 in the Middle East and North Africa (MENA) on Arab diasporas. This exploratory case study of the Tunisian expatriate communities in the immediate aftermath of the turmoil maps the changes in their associative networks and activities in France, Italy and Germany - the three principal European destinations for Tunisian migrants. It draws its data from a mixed methodological basis, using existing research papers, statistical data from the IOM and other IGOs as well as press and internet site analysis. Its empirical core however, is comprised of semi-structured interviews and background talks with members of the Tunisian expatriate communities in France, Italy and Germany in spring and summer 2014, i.e. in the key period between the adoption of the new Constitution and the Tunisian parliamentary elections of October.